La defensa ténica y la influencia en la voluntad del procesado a la hora de someterse a procedimiento abreviado - Carrión Wong, Vanessa Elizabeth (2018)
My main objective in the following case study is to give a good application of technical defense to the accused at the time of submitting to abbreviated procedure, bearing in mind that technical defense is the lawyer's performance and his duty to defend, advise and advise a Correct advice to the person who requires their services. The Constitution of the Republic of Ecuador in its Article 76 number 7, tells us: "The right of persons to defense shall include the following guarantees: a) No one may be deprived of the right to defense at any stage or degree of the procedure. b) Count on the time and with the adequate means to prepare your defense. c) Be heard at the right time and under the same conditions. d) The procedures will be public except for the exceptions provided by law. The parties may access all the documents and proceedings of the procedure. e) No one may be questioned, even for investigative purposes, by the Attorney General's Office, by a police authority or any other, without the presence of a private attorney or a public defender, or outside the premises authorized for the purpose. effect. f) To be assisted free of charge by a translator or interpreter, if she does not understand or does not speak the language in which the procedure is carried out. g) In judicial proceedings, to be assisted by a lawyer or lawyer of their choice or by a public defender or defender; You can not restrict access or free and private communication with your defender or defender. h) Present, verbally or in writing, the reasons or arguments that are believed to be assisted and replicate the arguments of the other parties; present evidence and contradict those that are presented against you. i) No one may be tried more than once for the same cause and matter